Some Explanations for the High Corporate Profits in the Philippine Pharmaceutical Industry - Echanis, Erlinda S.; Rodriguez, Rafael A. (Philippine Management Review, 2016)
This study finds the high profitability in the Philippine pharmaceutical industry to be primarily due to two factors:  One is the industry’s ability to increase prices, even under the adverse economic conditions of the 1982-1987 period, without adverse effects on total revenue.  The other factor is the relatively low investments in fixed assets in the industry, particularly plant and equipment, suggesting that pharmaceutical manufacturing in the Philippines is concentrated in the later part of the production process, e.g. the compounding and packaging stages.  The study also identifies possible industry reactions to the newly-passed Generics Law.